Reflections on the Learner Support Services for Rural-based Distance Learners at the Open University of Tanzania - Mahai, Lulu Simon (Papers in Education and Development, 2021)
Abstract This qualitative study explored rural - students ' experiences of support services at the Open University of Tanzania (OUT). Purposive and snowballing sampling procedures were used to obtain 30 respondents. Using data from observation, semi-structured interviews, and documentary review, the study found that OUT provides academic and non-academic support services through online and physical means at its regional centres. However, students in rural locations faced limited access of such services because some of the support services were more attuned to urban environment. Moreover, students in rural areas had to contend with socio-economic, academic, physical, technological and emotional challenges. This negatively impacted on their academic achievements. As such, there is a need to blend modern and traditional supportive means to improve the students ' accessibility to relevant support services in rural locations. Keywords: Open and Distance Learning (ODL), rural students, support services, Open University of Tanzania